DESIGN OF FACULTY LEADERSHIP DEVELOPMENT STRATEGY BASED ON COMPETENCY IN UNIVIVERSITI XYX - Amelia, Amelia (JISOS: JURNAL ILMU SOSIAL, 2023)
This qualitative research using case study approach aims to develop Leadership Development Strategy Design of Faculty Based Competence at XYZ University. Respondent from this research are rector, vice rector, dean, dan head of study program currently serving at XYZ University. Data collection techniques used in this study through surveys, interviews, and studies of internal documents. The result of the study showed: (1) the core competencies that should be held by the head of the study program and the dean of XYZ University are organizational commitment (OC), expertise (EXP), initiative (INT), conceptual thinking (CT), and customer service orientation (CSO), while the role competencies that must be owned are Directiveness (DIR), Planning and Organizing (PO), Developing Others (DEV), Team leadership (TL), Teamwork (TW), and Impact and Influence (IMP; (2) Competency assessment conducted using 3600 methode shows in general the weakness of dean competence are Organizational Commitment (OC), Customer Service Orientation (CSO), Directiveness (DIR), dan Teamwork and cooperation (TW), while the head of study program is weak on Expertise (EXP), Organizational Commitment (OC), Conceptual Thinking (CT), Impact and influence (IMP), Directiveness (DIR), and Teamwork and cooperation (TW).